Analisis Kualitas Pelayanan Publik Pada Pasien Peserta BPJS Studi Kasus RSU Puri Raharja Tahun 2016 - Pratamawisadi, I Gede Aditya; Pascarani, Ni Nyoman Dewi; Yudartha, I Putu Dharmanu (CITIZEN CHARTER, 2017)
ABSTRACT The BPJS program implemented in the Puri Raharja General Hospital was an effort from the government to equalize the health services. The objective was to find out the service quality for patients of BPJS participants in the case study of Puri Raharja General Hospital year 2016. Its research method was qualitative method by using data sources from primary data and secondary data. Its unit of analysis was looking for information regarding the analysis of public service quality on patients of BPJS. Informant determination technique used by the researchers used purposive sampling technique. Its data collection technique used by the researchers was interview and observation, while its technique to analyze the data was data reduction, data presentation, and draw the conclusion and result. This study used five dimensions tangible, reliability, responsiveness, assurance, empathy. The BPJS analysis program at Puri Raharja General Hospital seen from the overall aspects has been running well. The obstacle encountered in implementing BPJS Program was the lack of socialization from the BPJS parties about the service mechanism. It made the different perception between the hospital parties and patients of BPJS’ participants. Keywords: quality, public service, BPJS, five dimension